NIETSCHE, THE OVERHUMAN AND TRANSHUMANISM - Sorgner, Stefan Lorenz (2017)
Bostrom rejects Nietzsche as an ancestor of the transhumanist movement, as he claims that there were merely some “surface-level similarities with the Nietzschean vision” (Bostrom 2005a, 4). In contrast to Bostrom, I think that significant similarities between the posthuman and the overhuman can be found on a fundamental level. In addition, it seems to me that Nietzsche explained the relevance of the overhuman by referring to a dimension which seems to be lacking in transhumanism. In order to explain my position, I will progress as follows. First, I will compare the concept of the posthuman to that of Nietzsche’s overhuman, focusing more on their similarities than their differences. Second, I will contextualise the overhuman in Nietzsche’s general vision, so that I can point out which dimension seems to me to be lacking in transhumanist thought.